An overview of essential methods for preservation of sweet potato roots: a mini-review - Bambalele, Nonjabulo L.; Mditshwa, Asanda; Tesfay, Samson Zeray; Laurie, Sunette M; Shimelis, Hussein; Magwaza, Lembe Samukelo (Taylor & Francis, 2026)
Sweet potato is an essential and nutritious staple root crop in many parts of the world. This crop is multipurpose, humans consume the storage roots, while above-ground biomass is used for livestock feed. However, the roots are susceptible to sprouting during postharvest storage. Additionally, sweet potatoes are prone to postharvest diseases such as root rot, black rot, and soft rot. Various technologies have been used to preserve the quality of sweet potatoes. Studies have shown that techniques such as hot water, essential oils, and edible coatings effectively control postharvest disorders and diseases. Furthermore, treatments such as ethylene have been used to preserve sweet potato quality. However, negative outcomes such as root decay have been reported. As a result, the combination of 1-methylcyclopropene (1-MCP) and ethylene has been evaluated as a potential strategy for maintaining the quality of sweet potatoes. This mini-review examines the key postharvest techniques used for sweet potatoes. Also, the challenges of ethylene, 1-MCP, and hot water treatment are critically discussed.
Keywords: 30 Agricultural, Veterinary and Food Sciences; Biotechnology; 3001 Agricultural biotechnology; 3008 Horticultural production; 3108 Plant biology; Sweet potato; postharvest; shelf-life; sprouting; chilling injury; diseases